1991
DOI: 10.1055/s-2006-960092
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids, Phenolic Acids and Coumarins from the Roots ofAlthaea officinalis

Abstract: From the roots of ALTHAEA OFFICINALIS two flavonoid glycosides were separated. Phenolic acids and coumarins were investigated chromatographically. The structures of the compounds were established on the basis of acid hydrolysis and spectroscopic methods (UV, (1)H-NMR, (13)C-NMR) as hypolaetin 8-glucoside and the new flavonoid sulphate - isoscutellarein 4'-methyl ether 8-glucoside-2''-SO (3)K.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

1993
1993
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 7 publications
1
20
0
1
Order By: Relevance
“…Content of some flavonoids like hypolaetin-8-glucoside, isoquercitrin, kaempferol, quercetin and naringenin in the roots of A. officinalis has been reported [26,28,29]. The phytochemical evaluation of the extracts in the present study showed higher total flavonoid content for the extracts obtained by extraction with lower ethanol concentration in the mixed solvent (E2 and E3) (Figure 4).…”
Section: Abts Radical Cation Scavenging Assaysupporting
confidence: 59%
See 1 more Smart Citation
“…Content of some flavonoids like hypolaetin-8-glucoside, isoquercitrin, kaempferol, quercetin and naringenin in the roots of A. officinalis has been reported [26,28,29]. The phytochemical evaluation of the extracts in the present study showed higher total flavonoid content for the extracts obtained by extraction with lower ethanol concentration in the mixed solvent (E2 and E3) (Figure 4).…”
Section: Abts Radical Cation Scavenging Assaysupporting
confidence: 59%
“…According to literature, the root extract contains phenolic acids, in particular caffeic, p-coumaric, ferulic, p-hydroxybenzoic, salicylic, syringic, p-hydroxyphenylacetic and vanillic acid [26]. Our results revealed that the extract received with the lowest ethanol concentration (E2) contained the maximum phenolic content.…”
Section: Abts Radical Cation Scavenging Assaymentioning
confidence: 50%
“…Other constituents are about 0.2% flavone glycosides (Gudej, 1990), phenolic acids, the coumarin scopoletin (Gudej, 1991), starch, pectin (Hänsel et al, 1992), and tannins. Traditional use of aqueous extracts for dry cough due to irritation of the oral, pharyngeal or gastric mucosa after oral application is related to the bioadhesive effects of the polysaccharides to the epithelial mucosa, protecting the irritated cells from local irritation.…”
Section: Introductionmentioning
confidence: 99%
“…Federal Regulation,21 CFR 172.510. They contain many phenolic compounds and flavonoids, such as hypolaetin-8-g1ucoside, isoscutellarein 4'-methyl ether 8-g1ucoside-2'-sulfonate, caffeic acid, p-coumaric acid, ferulic acid, p-hydroxybenzoic acid, vanillic acid, syringic acid, and p-hydroxyphenylacetic acids (Gudej 1991). These compounds have some anti-inflammatory properties.…”
Section: Marshmallow Extractmentioning
confidence: 99%